Decreased Dolutegravir and Efavirenz Concentrations With Preserved Virological Suppression in Patients With Tuberculosis and Human Immunodeficiency Virus Receiving High-Dose Rifampicin. (21st July 2022) - Sekaggya-Wiltshire, Christine; Nabisere, Ruth; Musaazi, Joseph; Otaalo, Brian; Aber, Florence; Alinaitwe, Lucy; Nampala, Juliet; Najjemba, Letisha; Buzibye, Allan; Omali, Denis; Gausi, Kamunkhwala; Kengo, Allan; et al.
Abstract: Background: Higher doses of rifampicin may improve treatment outcomes and reduce the duration of tuberculosis (TB) therapy. However, drug–drug interactions with antiretroviral therapy (ART) and safety in people with human immunodeficiency virus (HIV) have not been evaluated. Methods: This was a randomized, open-label trial where newly diagnosed TB patients were randomized to higher (35 mg/kg) or standard (10 mg/kg) daily-dose rifampicin. ART treatment–naive patients were randomized to dolutegravir- or efavirenz-based ART. At week 6, trough dolutegravir or mid-dose efavirenz plasma concentrations were assayed. HIV viral load was measured at week 24. Results: Among 128 patients randomized, the median CD4 count was 191 cells/mm 3 . The geometric mean ratio (GMR) for trough dolutegravir concentrations on higher- vs standard-dose rifampicin was 0.57 (95% confidence interval [CI], .34–.97; P = .039) and the GMR for mid-dose efavirenz was 0.63 (95% CI, .38–1.07; P = .083). There was no significant difference in attainment of targets for dolutegravir trough or efavirenz mid-dose concentrations between rifampicin doses. The incidence of HIV treatment failure at week 24 was similar between rifampicin doses (14.9% vs 14.0%, P = .901), as was the incidence of drug-related grade 3–4 adverse events (9.8% vs 6%). At week 8, fewer patients remained sputum culture positive on higher-dose rifampicin (18.6% vs 37.0%, P = .063). Conclusions: Compared with standard-dose rifampicin, high-dose rifampicin reduced dolutegravir and efavirenz exposures, but HIV suppression was similar across treatment arms. Higher-dose rifampicin was well tolerated among people with HIV and associated with a trend toward faster sputum culture conversion. Clinical Trials Registration: NCT03982277. Abstract : We demonstrated that high-dose rifampicin (35 mg/kg) reduced dolutegravir and efavirenz exposures without compromising virological suppression in patients with human immunodeficiency virus (HIV). High-dose rifampicin was well tolerated among people with HIV and associated with a trend toward faster sputum culture conversion.